"Sharks in Your Hands"—A Case Study on Effects of Teaching Strategies to Change Knowledge and Attitudes Towards Sharks. Issue 3 (2nd July 2016) - Lee, Hung-Shan; Liu, Shiang-Yao; Yeh, Ting-Kuang
Abstract : This study was designed to exemplify how hands-on based teaching strategies enhanced students' knowledge and positive attitudes towards sharks. Hands-on activities for sharks' biological and morphological features were carried out. Eleven elementary school students from a remote area in Taiwan were recruited and assigned to the hands-on condition. They were encouraged to draw pictures of sharks before and after the instruction as the main data for pre- and post-test comparison. Two years later, the retention test and attitude inventory towards sharks were implemented. The results revealed that large effect size emerged for both the post-test and retention test. In regards to attitude inventory, students involved in hands-on activities also significantly outperformed the baseline group. Many of them have taken notice of television programs and books about sharks or marine ecology since the hands-on activities, indicating the instruction had a beneficial impact on their extracurricular lives. Empirical findings of this study suggest hands-on instruction is a powerful strategy for learning, both for immediate and prolonged effects on improving students' knowledge and attitudes toward sharks.